Kompetensi Tenaga Kerja Kontraktor terhadap Implementasi SMKK Proyek Pembangunan Gedung Fakultas Kedokteran Gigi Universitas Andalas Tahun 2025 - Daniel Khaliq; Taufika Ophiyandri; Benny Hidayat (Universitas Batanghari Jambi, 2026)
The construction industry is recognized as a sector with a high risk of occupational accidents due to the complexity of work activities, the involvement of a large workforce, and the use of hazardous equipment and working methods. To control these risks, the Indonesian government mandates the implementation of the Construction Safety Management System (SMKK) through Regulation of the Minister of Public Works and Housing No. 10 of 2021. However, its implementation in the field is still strongly influenced by the competence of contractor workers, particularly in terms of knowledge, skills, and attitudes toward occupational safety. This study aims to analyze the competence of contractor workers in supporting the implementation of SMKK at the Integrated Skills Laboratory Building Project of the Faculty of Dentistry, Universitas Andalas, in 2025. A descriptive research design with a mixed-methods approach was employed, involving quantitative data collection through questionnaires and qualitative data obtained from observations and interviews. Descriptive analysis was conducted to assess workers’ levels of knowledge, skills, and attitudes toward SMKK implementation. The results indicate that workforce competence is generally categorized as moderate to good; however, weaknesses remain in the consistency of safe work procedure implementation and safety discipline on site. Based on these findings, this study recommends strengthening behavior-based safety training, improving supervisory practices, and implementing continuous workforce development to enhance the effectiveness of SMKK and promote a sustainable safety culture in construction projects.